MISSION IN THE NEW TESTAMENT: ITS THEOLOGICAL BASIS AND IMPLEMENTATION IN THE CHURCH TODAY - Alvionita Indasari Taidi; Lumentah, Henokh; Laura Takalamingan; Zefanya Montong (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
This article examines the theological basis and implementation of mission in the New Testament and its relevance to the church today. This research is motivated by the crisis of missionary identity in the church amid the challenges of globalization, secularization, ecological crisis, and relativism of truth. The main focus of this research is on the concept of missio Dei, which emphasizes that mission originates from the initiative of the Triune God, not solely from the church. The objective is to analyze the theological foundations of mission in the New Testament and how the church lives out its calling as a sent community. The method used is qualitative, employing a literature review approach to the Bible, theological literature, and academic journals. The main findings show that mission is the identity of the church, not just one of its programs. Mission in the New Testament is Trinitarian, holistic, and includes the proclamation of the Gospel, acts of love, social justice, and the formation of an inclusive community. The early church set an example through its living witness and cross-cultural evangelism. In the contemporary context, implementing mission requires contextual approaches such as digital ministry, social empowerment, discipleship, and interdenominational collaboration. The synthesis of key ideas emphasizes that mission cannot be separated from the existence of the church; without mission, the church loses its identity. In conclusion, the church today is challenged to return to the contextual, transformative, and Spirit-led mission of the New Testament to remain relevant in an ever-changing world.